Effects of second language exposure in the preschool context on first language skills and executive functions of 4 and 5 year olds - Erciyes, Aslı Aktan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
The emerging situation in the urban Turkish context involves the acquisition of an esteemed L2 in a context where L1 is the majority language which is also of high value, by children from advantaged social backgrounds. This makes the situation different from those studied most often and is therefore worth exploring. The present study asks whether there are negative or positive consequences of full time exposure to L2 in preschool on L1 and on executive functioning, where the exposure starts as early as age 3. Two age groups of 106 children, 4 year olds and 5 year olds, were chosen to participate in the study according to the school type they attend to, Turkish instruction schools and English Instruction schools. Participants performed the following tasks; for language competence: TEDİL (Test of Early Language Development- Turkish version), TELD-3 (Test of Early Language Development, English version), Narrative Skills Task and for executive functioning: DCCS, Bear/Dragon, Day/Night, Gift- Delay, Snack-Delay. The first hypothesis that there will be difference due to age in L1 and L2 competence was supported. For L1, older group performed better in both TELD-3-T and Narrative Skills Task. For L2, there was also age effect on L2 measured by TELD- 3. Older children were better than younger ones. The second hypothesis which stated that L2 competence of children who attend English instruction schools would be better than the ones who attend Turkish instruction schools was also supported. The third hypothesis which predicted that there would be a difference in L1 measured by TEDİL due to amount of exposure in favor of those who are attending Turkish Instruction schools was not supported. The fourth hypothesis that there would be difference in L1 measured by Narrarive Skills task due to amount of exposure in favor of those who are attending Turkish Instruction schools was not supported either. In terms of the complexity of the linguistic forms used in the stories, the amount of English spoken at home predicted the use of infinitival clauses, in English where speaking more English was associated with higher scores. The last hypotheses which predicted that there would be positive effects of L2 competence on executive functioning tasks was partially supported. For DCCS and composite score of gift and snack delay, there was a significant effect of L2 competence. Higher competence was associated with higher scores. The results were also discussed in the light of SES and mother’s education as well as English activities carried out at home.
Keywords: English language -- Study and teaching (Preschool) -- Foreign speakers.; Bilingualism in children -- Turkey.